Scientific writing = thinking in words - Lindsay, D. R. (CSIRO Publishing, 2020)
Telling people about research is just as important as doing it. But many competent researchers are wary of scientific writing, despite its importance for sharpening scientific thinking, advancing their career, obtaining funding for their work and growing the prestige of their institution. This second edition of David Lindsay's popular book Scientific Writing = Thinking in Words presents a way of thinking about writing that builds on the way good scientists think about research. The simple principles in this book will help you to clarify the objectives of your work and present your results with impact. Fully updated throughout, with practical examples of good and bad writing, an expanded chapter on writing for non-scientists and a new chapter on writing grant applications, this book makes communicating research easier and encourages researchers to write confidently. It is an ideal reference for researchers preparing journal articles, posters, conference presentations, reviews and popular articles; for students preparing theses; and for researchers whose first language is not English.
Includes index
Keywords: Technical writing -- Study and teaching.; Communication of technical information.; elektronické knihy; electronic books